2015
DOI: 10.1093/bioinformatics/btv416
|View full text |Cite
|
Sign up to set email alerts
|

RxnSim: a tool to compare biochemical reactions

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…We repeated the analysis from the previous section using the standard reaction difference fingerprint (Methods), which is used in structure similarity methods such as RxnSim (36) and RxnFinder (37), to assess the benefits of introducing the information about the reactive site of substrates into the reaction fingerprints. A comparison of the two sets of predictions on 5,049 non-orphan reactions showed that the predictions obtained with BridgITmodified fingerprints were significantly better than the standard ones.…”
Section: Bridgit Reaction Fingerprints Offer Improved Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We repeated the analysis from the previous section using the standard reaction difference fingerprint (Methods), which is used in structure similarity methods such as RxnSim (36) and RxnFinder (37), to assess the benefits of introducing the information about the reactive site of substrates into the reaction fingerprints. A comparison of the two sets of predictions on 5,049 non-orphan reactions showed that the predictions obtained with BridgITmodified fingerprints were significantly better than the standard ones.…”
Section: Bridgit Reaction Fingerprints Offer Improved Predictionsmentioning
confidence: 99%
“…In addition, these methods are not suitable for the annotation of de novo reactions since current pathway prediction tools only provide information about enzyme catalytic biotransformations and not about their sequences. These shortcomings motivated the development of alternative computational methods based on the structural similarity of reactants and products for identifying candidate protein sequences for orphan enzymatic reactions (30,33,(36)(37)(38)(39)(40). The idea behind these approaches was to assess the similarity of two enzymatic reactions via the similarity of their reaction fingerprints, i.e., the mathematical descriptors of the structural and topological properties of the participating metabolites (41), which could eliminate the problems associated with non-matching or unassigned protein sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarity between chemical reactions, referred to as reaction similarity, can be calculated at multiple levels: Transformation level similarity is computed by considering only the atoms and bonds that are undergoing transformation, at different degrees of neighborhood information [ 12 ]. Reaction level similarity considers molecular information of the entire substrates and products constituting a biochemical reaction [ 13 ]. Assessing reaction similarity as transformation level enables classification of enzyme function based on reaction mechanism [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 14 We have reported an approach to address these limitations using kernel PCA embedded vector representations of molecules and principals of compositional semantics from computational linguistics. 15 While computational methods exist to compare, classify, and search enzymatic reactions 16 21 , they frequently rely on direct comparison of molecular fingerprints as well as specific bond or atom changes within the molecule. Our approach allows for the representation of chemical transformations as algebraic expressions of chemical structure vectors.…”
Section: Introductionmentioning
confidence: 99%